EMPREGO DE STENTS CEREBRAIS NAS PATOLOGIAS CEREBROVASCULARES - Laís Rocha Lopes; Miriã Moreira Cardoso Severino; Ana Laura Stahlhoefer; Ana Carolina Oliveira Vilela; Antenor Tavares de Sá Júnior (UniEVANGÉLICA, 2015)
Objective: To understand the applicability and characteristics of the stents for the treatment of cerebrovascular pathologies in order to understand its viability for the therapy. Methods: Scientific articles were used based on electronic search as PubMed, Scientific Electronic Library Online (SciELO), Intechopen, Medscape. An international and up to date source of articles was used. Results: Cerebrovascular diseases have emerged as the second most important cause of mortality worldwide, from this principle we observe the importance of this study. Recently, as a solution form, stents have become a major treatment option for difficult and not feasible cerebral aneurysms single winding. Intracranial stents serve as a bridge to the neo-endothelialization by providing a reduction in blood flow into the aneurysm. The use of stents for treatment should be seriously analyzed according to their feasibility, the knowledge of the professional about their brands, features and deployment techniques, and theoretical part of the professional needs to have dexterity to the application of an intracranial stent. Conclusions: This review raises an awareness of this subject, starts from the concept of cerebrovascular disease and aneurysms as well as the genesis of the stents, progressing to elucidate all product brands and specific characteristics of each, ending with its applicability, as well as making clear the purpose and mechanism of stents.